Women in Conflict Communication Perspective (Case Study of the Role of Women in Maintaining Harmony in Manado) - Suzy Azeharie; Wulan Purnama Sari; Muhammad Gafar Yoedtadi (Jurnal Komunikasi, 2024)
Cultural diversity in Indonesia is analogous to a double-edged sword. On the one hand, it can be seen as a source of strength, but on the other hand, it can be seen as a weakness. In April 2022, SETARA Institut, a non-governmental organization for democracy and peace, announced 10 cities in Indonesia that were rated as having the highest level of tolerance, one of which was Manado. Minahasa society adheres to the Sitou Timou Tumou Tou philosophy. In this philosophy there is openness, mutual respect, mutual assistance and assistance. Multicultural societies have a tendency towards conflict. In this case, women activists in Manado play a role in establishing harmonization. The research aims to discover the role of women in maintaining harmony in Manado, as well as the conflict communication used to prevent conflict. This research uses a descriptive qualitative approach with a case study method. The object of this research is the role of Manado women in maintaining harmony and conflict management. The subject of Manado women's activists. This research uses several data collection methods, including interviews, observation, literature study and online data tracing. The research results show that women activists actively carry out interfaith or interfaith dialogue with various social organizations, especially Islamic organizations. Women activists also took the initiative to establish the Peace Love Movement which seeks to build dialogue and make dialogue a part of their lifestyle. In order to build public awareness of multiculturalism, every Human Rights Day, namely December 10, the Love and Peace Movement holds a Diversity Festival.